MUSLIM URBAN AND RELIGIOUS MINDSET: ASSESSING RELIGIOUS MODERATION AMIDST THE DIGITAL RADICALISM WAVE - Komarudin, Komarudin (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Urban Muslims, or those living in metropolitan areas, face unique social and cultural dynamics in their religious lives. Unlike rural Muslim communities, which are generally more socially and religiously homogeneous, urban Muslims live amidst cultural diversity, interfaith interactions, and high exposure to globalization; (2) Purpose of the Study: This study explores the religious mindset of urban Muslims in Makassar and Bandung in responding to digital radicalism; (3) Methods: Using a qualitative phenomenological approach, data was collected through multiple sources to capture diverse perspectives; (4) Results: The findings reveal that urban Muslims in Makassar tend to selectively consume religious content that emphasizes moderation and tolerance, despite challenges posed by social media algorithms that promote exclusive content. Meanwhile, urban Muslims in Bandung demonstrate a stronger preference for academic and open-dialogue-based study communities, fostering a more rational and contextual understanding of Islam; and (5) Conclusions: The role of digital communities is critical in shaping religious perspectives, as many individuals actively filter and compare various sources to counteract judgmental narratives. However, exposure to conservative content remains a concern in both cities. Strengthening digital literacy and structured religious education is crucial to promoting an inclusive understanding of Islam in the digital era.